Relationship between transition of fracture mode of carbon fiber-reinforced plastic and glass transition temperature of its resin. (3rd March 2016) - Muramatsu, Mayu; Harada, Yoshihisa; Suzuki, Takayuki; Niino, Hiroyuki
Abstract : In this study, the correlation between the stress–strain behavior of a carbon fiber-reinforced plastic (CFRP) and the temperature at which the heat-affected zone (HAZ) is generated is investigated. First, CFRP ([−45/45]2s laminate) specimens were heated at several temperatures to induce thermal damage, i.e. a HAZ. Subsequently, tensile tests were conducted on the specimens with thermal damage. Then, microscopy and X-ray measurements were carried out to discuss the stress–strain responses from a microscopic viewpoint. The results of strain measurement during thermal treatment indicated that the strain increases with increasing temperature. The tensile tests showed that the CFRP specimens subjected to thermal damage during heating at a high temperature fractured in the ductile mode, whereas the fracture mode of the CFRP specimens with low-temperature thermal damage was discontinuous. Microstructure observation using X-ray tomography showed that the debonding between the carbon fibers and the resin matrix induced by heating to above the glass transition temperature was responsible for the continuous fracture mode.